Impact of step length asymmetry on walking energetics in women with hip Osteoarthritis: A pilot study. (2nd December 2021) - Huang, Chun-Hao; Aydemir, Burcu; Jalasutram, Anusha; Kabir, Ike; Foucher, Kharma C.
Abstract: A step length difference between the involved and uninvolved limbs in participants with hip osteoarthritis (OA) has been reported. The implications of step length asymmetry on other aspects of walking mechanics are as yet unknown. The objective of the current study was to evaluate the consequences of step length asymmetry on motion of the center of mass (COM) and energy cost of walking. We hypothesized that (i) increased step length asymmetry is associated with decreased mechanical energy exchange; (ii) decreased mechanical energy exchange is associated with increased O2 cost; (iii) increased step length asymmetry is associated with increased oxygen O2 cost during walking in women with hip OA. We evaluated 24 women with unilateral hip OA using motion analysis as participants walked on a treadmill at self-selected speeds. Kinematic data were collected to compute step length asymmetry and mechanical energy exchange through the motion of COM. We also used a portable metabolic system to measure the energy cost of walking simultaneously. We used Pearson correlations and linear regression to test our hypotheses. We found that more asymmetric step lengths were associated with lower mechanical energy exchange (R 2 = 0.231, p = 0.017). More mechanical energy exchange was associated with lower O2 cost during gait (R 2 = 0.284, p = 0.009). Mechanical energy exchange predicted 54.5% of the variance in O2 cost after adjusting for self-selected walking speed. Findings suggest that modifying step length asymmetry could enhance metabolic gait efficiency indirectly by improving mechanical energy exchange in participants with hip OA.